Choosing a starting professional trajectory: job-education mismatch effect - A. D. Melnik; A. E. Sudakova; N. L. Antonova (Образование и наука)
Introduction. The research problem pertains to the entire system of vocational education; however, it is illustrated through the example of higher education. The job-education mismatch effect refers to the phenomenon where university graduates, regardless of whether they hold a bachelor’s or master’s degree, choose jobs that do not align with their level of education. Aim. The present article aimed to provide a theoretical conceptualisation and empirical analysis of the job-education mismatch effect at various stages of the transition from university to the labour market (six months, one year, and 7–10 years). During these stages, university graduates can evaluate how their university experiences have influenced their career choices. Methodology and research methods. The empirical sample comprised monitoring surveys of university graduates from a large Russian university conducted between 2017 and 2022, six months after graduation (n = 7,706). Additionally, semi-structured interviews were carried out with respondents in 2021 (n = 10). This information was further supplemented by semi-structured interviews with middle-aged workers conducted 7 to 10 years after graduation (n = 10) and by monitoring the effectiveness of Russian universities based on the number of enterprises serving as practical training bases under agreements established with universities from 2020 to 2022. Results. The results of the study reveal differences in the selection of initial professional trajectories among university graduates with varying educational backgrounds. The typology of these choices categorises graduates into four groups: achievers, indifferentists, rationalists, and self-realisers. The findings, derived from a quantitative assessment of the university-business partnership network, raise concerns about how this network is managed by universities, especially within federal universities and those adhering to the industrial leadership track outlined in the programme Priority-2030. Scientific novelty. The research materials contribute to the development of scientific insights into the behaviour patterns of young people as they make professional choices in the context of labour market variability. Practical significance. The reduction of the job-education mismatch can be enhanced through project-based learning, which fosters direct interaction between industry partners and students. This engagement increases interest in the cultivation and early recruitment of proactive students for the development of high-tech industries and intellectual services.